2019
DOI: 10.18203/issn.2454-5929.ijohns20191741
|View full text |Cite
|
Sign up to set email alerts
|

CT scan vs nasal endoscopy findings in the diagnosis of chronic rhinosinusitis: our experience

Abstract: <p class="abstract"><strong>Background:</strong> Diagnostic nasal endoscopy and CT imaging are both widely used essential diagnostic tools for chronic rhinosinusitis (CRS). This study analyses their individual roles in the management of CRS as well as the degree of correlation between the two.</p><p class="abstract"><strong>Methods:</strong> A prospective observational comparative study was conducted in the Department of Otorhinolaryngology, Mahatma Gandhi Hospital, Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 12 publications
2
8
0
Order By: Relevance
“…5 Diagnostic endoscopy has been recommended for diagnosis of chronic rhinosinusitis by EPOS 2012. 3 The findings of present study were supported by findings of Baruah et al (2019) in which deviated nasal septum (60.7%) was the most common finding observed on DNE in patients with CRS. 6 Also, They also observed pneumatized middle turbinate or concha bullosa in 31.3% cases, paradoxical middle turbinate in 20% and accessory ostium in 32.3% cases.…”
Section: Discussionsupporting
confidence: 86%
“…5 Diagnostic endoscopy has been recommended for diagnosis of chronic rhinosinusitis by EPOS 2012. 3 The findings of present study were supported by findings of Baruah et al (2019) in which deviated nasal septum (60.7%) was the most common finding observed on DNE in patients with CRS. 6 Also, They also observed pneumatized middle turbinate or concha bullosa in 31.3% cases, paradoxical middle turbinate in 20% and accessory ostium in 32.3% cases.…”
Section: Discussionsupporting
confidence: 86%
“…14,15 Frontal involvement was seen in 32% of the cases in the present study, while Baruah et al reported a 23% involvement of the same. 13 The least affected sinuses in our study was frontal an sphenoid. This was corroborated by studies by Baruah et al and Zojaji et al, who also reported the same.…”
Section: Discussionmentioning
confidence: 60%
“…This was corroborated by studies by Baruah et al and Zojaji et al, who also reported the same. 13,16 Maxillary sinus involvement was observed in another study by Kaku and Harugop in 56.66% patients on the right side and in 60% of the patients on the left side. 17 The most common pathology of the osteomeatal complex was polyps on nasal endoscopy seen in 17 (34%) of the cases.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations